Effect of Dose and Time of Nitrogen Application on Growth and Yield of Sesamum (Sesamum indicum L.) Under Irrigated Conditions - Aruna, E.; Kumar, K. Sunil (International Journal of Economic Plants, 2023)
The experiment was conducted during rabi season from November to January months of 2020–21 in the farm of Agricultural Research Station, Utukur, Kadapa, Andhra Pradesh, India to study the growth and yield performance of sesame under different levels and times of nitrogen application. The treatments included four levels of nitrogen viz., 40, 60, 80 and 100 kg ha-1 and four application timings as 50:50 basal and 30 DAS, 25:75 basal and 30 DAS, 25:37.5:37.5 basal, 20 and 40 DAS and 0:50:50 basal, 20 and 40 DAS which were laid out in split plot design with levels of nitrogen in main plots and time of nitrogen application in sub plots in three replications. The test variety YLM-66 was mixed with sand in 1:3 proportion and sown at a spacing of 30×10 cm2. Taller plants were recorded with application of 100 kg N ha-1 which was on par with 60 and 80 kg ha-1 and the number of branches per plant was not influenced significantly by nitrogen. The number of capsules plant-1, number of seeds capsule-1 and seed yield was higher with application of 80 kg N ha-1 indicating this as an optimum of nitrogen fertilizer in contrast to the present recommended dose of 40 kg N ha-1and regarding the time of application, and number of splits, application of 80 Kg N ha-1 in three splits in the ratio of 25-37.5-37.5 at basal, 20 and 40 days after sowing is recommended for getting higher seed yield in sesamum. Under irrigated conditions in YSR Kadapa district of Andhra Pradesh.